Emotional labor, fatigue, and presenteeism in Chinese nurses: the role of organizational identification - Zheng Ren; Chao Zhou; Xiumin Zhang; Aoqi Yang; Wenjun Li; Hongjian Liu (BMC, 2024)
Abstract Background Presenteeism has become a significant issue related to health. However, the effect of fatigue and organizational identification on the relationship between emotional labor and presenteeism among Chinese nurses remains unclear. This study aims to explore the correlation of Chinese nurses' emotional labor, fatigue and organizational identification with presenteeism, and to analyze the mediating effect of fatigue and the moderating effect of organizational identification on the relationship between emotional labor and presenteeism. Methods A cross-sectional study was performed from June to October 2022 in Changchun City, Jilin Province, China. In total, 1,630 nurses were asked to complete a range of self-administered questionnaires, including the Emotional Labor Scale, the Fatigue Scale, the Organizational Identification Scale and the Stanford Presenteeism Scale. Besides, the PROCESS macro and multiple linear regression were used for moderated mediation analysis. Results Emotional labor (r = 0.108, P < 0.001) and fatigue (r = 0.475, P < 0.001) were positively correlated with presenteeism, while organizational identification (r = -0.261, P < 0.001) was negatively correlated with presenteeism. The effect of emotional labor on presenteeism was partially mediated by fatigue (Effect = 0.014, 95% CI = [0.007, 0.021]). Additionally, the relationship between emotional labor and fatigue was moderated by organizational identification (P = 0.018 for the interaction term). Conclusions Fatigue and organizational identification have mediating and moderating effects on the relationship between emotional labor and presenteeism, respectively. Targeted support measures should be taken to improve the presenteeism of nurses. Nursing managers can relieve the psychological pressure and fatigue of nurses by establishing emotional release channels, and improve the presenteeism of nurses through enhancing organizational identification.